Robust digital control of a class-D amplifier with low switching frequency for vibration generator - Kazuki Hanabusa (2018)
© 2017 IEEE. In late years a class-D amplifier has been used for a vibration generator and IGBT is often used for the switching element of the class-D amplifier. However, since the switching frequency of IGBT is limited low, it is difficult to make the bandwidth of the class-D amplifier wide. The bandwidth 5 kHz is required by the amplifier for the vibration generator with load impedance 2 -8 ω. In this paper, it is shown that the bandwidth 5 kHz of the class-D amplifier can be realized by applying A2DOF control with the switching frequency 50 kHz. Since the output PWM frequency of a bridge circuit increase twice as much as IGBT switching frequency by using a double carrier PWM generating system, the sampling frequency of a controller can be increased twice as much as the switching frequency, i.e. is 100 kHz. Then the bandwidth 5 kHz of the class-D amplifier for the vibration generator with load impedance 2 - 8 ω can be realized by devising how to design A2DOF control. The controller is implemented in a DSP and it is shown from experiment that the desired performance is attained enough.